Kerajinan Batik dan Pewarnaan Alami - Alamsyah Alamsyah (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
BATIK – craft is a cultural heritage of Indonesia which existence keep growing each day. It is characterized by the existence of batik craft in various regions with their own characteristics. As a cultural heritage, batik craft had been around since the time of the kingdom era in our nation. Before the discovery of synthetic materials technology, batik coloration has always been using natural colors that are available in Indonesia. Natural coloration can be taken from tinggi wood, tegeran plant, teak leaf, indigo plant, secang, mahogany, and other plants. As the times progressed, natural coloring began to be replaced and abandoned by the craftsmen. Crafters use synthetic coloring starting in the early 20th century. Currently there is an awareness to return to the natural coloring because it is considered to be more environmentally friendly and cheaper. The use of natural coloring also pushes batik selling value higher when compared to the one using synthetic color